OC-007 Enhancing detection and treatment of viral hepatitis and liver fibrosis in vulnerable and homeless adults through dedicated hostel-based liver service: valid (vulnerable adults liver disease) study. (17th June 2017) - Hashim, A; Macken, L; Worthley, T; Aithal, GP; Verma, S
Abstract : Introduction: Homeless adults, a disenfranchised and stigmatised cohort, are particularly at risk of chronic liver disease (CLD) due to high prevalence of alcohol/substance misuse. Risk of CLD rises further with increasing age. However, this vulnerable group don't engage with or access hospital services. We have designed a community liver service in Southeast England, with an aim of detecting, staging and treating CLD in homeless adults aged > 40 years. Method: In October 2015, we set up a new service at two major homeless hostels and a primary care practice that caters to the homeless. As a part of prospective cohort study, we enrolled consecutive aged > 40 years. Each individual was offered alcohol (AUDIT questionnaire) and substance misuse assessment, blood borne virus (BBV) tests and mobile Transient Elastography (TE). Clinically significant hepatic fibrosis (CSHF) was defined as liver stiffness measurement (LSM) ≥8 kPa Results: Till date 71 individuals have been enrolled. Mean age of participants was 51 years±5.8%–82% were males. Forty one (58%) were homeless or living in hostels at the time of recruitment. Positive hepatitis C virus (HCV) antibody was detected in 28 participants (39.4%), while HIV antibody and hepatitis B core antibody were found in 2 (2.8%) and 12 participants (17%) respectively. Twenty six out of 28 (93%) individuals with positive HCV antibody consented to further testing, twenty (77%) having a positive HCV PCR. The prevailing genotypes were 1a (55%) and 3a (45%). The majority (75%) were drinking alcohol in excess of recommended guidelines, the AUDIT questionnaire revealing that 33 individuals (46%) had alcohol dependence (scores of >20/40). Fifty seven (80%) had history of current/past substance misuse with 24 (66%) individuals having a formal diagnosis of mental illness. Of the 71 participants, 22 (31%) had CSHF (LSM ≥8 kPa) with 13 (18%) having advanced fibrosis (LSM > 13 kPa. The main aetiologies for CLD were alcohol, HCV or both. Of the 20 individuals with positive HCV RNA, five commenced community based HCV treatment with direct acting antivirals with two more currently being worked up for therapy. Conclusion: Preliminary results of the VALID study show a high prevalence chronic HCV infection and CSHF in vulnerable/homeless people over 40 years of age. We found an excellent uptake of community based liver service from this group and mobile TE was perceived as a powerful tool to facilitate engagement. Our initial results endorse the success of this easy to replicate community model of liver care for vulnerable adults. Disclosure of Interest: A. Hashim: None Declared, L. Macken: None Declared, T. Worthley: None Declared, G. P. Aithal: None Declared, S. Verma Conflict with: Dunhill Medical Trust, Gilead